ANALISIS KEMAMPUAN METAKOGNISI DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA PADA PESERTA DIDIK KELAS XI SMA - Wahyuni, Annisa (Jurnal Edukasi dan Penelitian Matematika, 2023)
The research background was the inability of students to monitor the concepts and strategies used in accordance with the problems given, like the inability of students to control the results obtained. Besides that, students' metacognitive ability to math problem solving is still low. The research purpose was to determine students' metacognitive abilities in mathematical problem solving problems. This research type was exploratory qualitative research. The research subjects were class XI students of SMA Negeri 9 Padang in the 2022/2023 academic year, which consisted of 24 students. Qualitative methods are used in this study because the problems encountered are holistic. Data collection was condcuted by administering tests, questionnaires, and interviews. The main instruments in this research were researchers and supporting instruments in consist of matrix metacognitive tests, metacognitive ability questionnaires, and interview guides. The techniques for data analysis were reduction of data, presentation of data, and conclusions in drawing. The validity of data guarantee technique is technical triangulation. The research results shown that there are three categories of students' metacognitive abilities, namely high, medium, and low metacognitive abilities. The highest percentage is students with high metacognitive abilities, followed by metacognitive abilities in medium and low. Students who have high metacognitive abilities fulfill every planning, monitoring, and evaluation activity. Students who have moderate abilities of metacognition have fulfilled the indicators in planning activities, while in monitoring and evaluation activities there were still indicators that have not been fulfilled. Students who have low abilities of metacognitive still have many indicators on abilities of metacognitive that have not been able to be met. Keywords– Metacognition Abilities, Problem Solving Questions